The Naked Ape Is Still an Ape: Contradictions in Conservation Biology - Miguel Ferrer (Diversity, 2022)
The scientific discipline known as Conservation Biology was established in the early 1980s with the aim of becoming a tool for the management of biodiversity and ecosystems on the planet. The reality today is that there is no consensus among researchers even as to which species and spaces we should protect and how or what are the ecosystem services that we should preserve. I believe that Environmental Thinking is seriously affecting Conservation Biology. The two most influential schools in environmental philosophy thought have been land ethics and deep ecology. In both, especially in deep ecology, we still consider human beings as separate from nature and “bad” from a moral point of view.Intrinsic values beliefs oblige us to avoid any extinction, even if this is a necessary part of the evolutionary process. Both shortcomings are seriously limiting our ability to focus on the real problem. We should overcome the man–nature dichotomy by understanding that we are neither more nor less than a part of it. When we talk about protecting nature, we are actually talking about protecting human–nature habitats, maintaining conditions that make life possible for our species in a world full of opportunities and living beings, including ourselves.